KEMITRAAN DI SEKTOR PERIKANAN TANGKAP: STRATEGI UNTUK KELANGSUNGAN USAHA DAN PEKERJAAN - Devi Asiati; NFN Nawawi (Research Centre for Population, Indonesian Institute of Sciences, 2016)
Partnership and empowerment development of fishermen community is one way that can be taken to ensure the continuity of business and employment in the fishery sector. This attempt also promotes the improvement of social and economic condition of fishermen community through income enhancement and property alleviation, reduces fisherman’s dependency on traditional capital institution, and achieves more equitable and sustainable development. This paper aims to review the concept of partnership and empowerment of workers in the fishery sector and to analyze alternative policy strategies of fishermen’s partnership and employment through strengthening the internal aspect (institutional approach) and the external aspects (infrastructure and capacity support). The analyzed data derived from field research in Tegal and Cilacap, Central Java in 2013 and 2014. This paper confirms that the synergy between the government, fishermen, and business has a very important role in supporting the successful implementation of the partnership program and the empowerment of fishermen. Furthermore, it is important to establish and improve capabilities of fishermen group in local level, to supervise and monitor the implementation of activities involving all fisheries’ stakeholders, and to establish strategic polices that support fishermen’s autonomy in fisheries equipment ownership, the business capital, marketing network, and production process.